The Effect of Dhikr Relaxation Therapy on Reducing Anxiety Levels of ER and ICU Nurses in Public Hospitals - Baroroh, Ema Zati; A’yuni, Qurratul (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2024)
Anxiety problems that occur in UGD and ICU nurses are very vulnerable to occurring because of the many demands they have to face. The aim of this study was to reveal the effect of dhikr relaxation therapy on reducing anxiety levels in ER and ICU nurses. One of the reasons this research topic is important is to provide knowledge to ER and ICU nurses that anxiety can be overcome by carrying out dhikr relaxation therapy. The research design uses a quantitative and qualitative approach to the type of experimental psychology, namely pre-experimental design using a One-group Pretest-Posttest Design. The hypothesis of this research is that there is an effect of dhikr relaxation therapy on reducing anxiety levels in ER and ICU nurses. Data were collected using the TMAS anxiety scale with a significant value of 0.028 (p < 0.05), which shows that there are differences in anxiety in ER and ICU nurses before and after training. Thus, dhikr relaxation therapy training is effective in reducing anxiety levels in ER and ICU nurses.